La honte au corps : vers le réel de la performance S/M - Jacques Brunet-Georget (Genre, Sexualité et Société)
Following Eve Sedgwick, Lynda Hart looks into the paradoxical role of shame as what disrupts the narcissistic identification while making possible a renewal of the bond to the other. She thus questions the erotic interest within the context of bodily sadomasochistic performance - the lesbian one in particular. However, her intention to provide a non-ontological, but erotic, definition of shame, is contradicts some of her presuppositions. Using what Lacan calls “hontologie”, and bringing up the psychoanalytical category of the “real”, the point is to define a “shame of living” that is very different from guilt: a way for the subject to go through their identifications so as to feel the limit which sets the substance of their being. The example of Bob Flanagan, the famous “supermasochist”, will allow us to show how a particular experience of shame can contribute to an erotic renewal from the point where a subject finds themselves on the threshold of their own disappearance.